Form and faith in Victorian poetry and religion - Blair, Kirstie (Oxford : Oxford University Press, 2012)
This study explores Victorian poetry in relation to Victorian religion, with particular emphasis on the contemporary debates over the use of forms in worship. It discusses major Victorian poets - Tennyson, the Brownings, Rossetti, Hopkins, Hardy - and also argues that their work was influenced by a host of minor and less studied writers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English poetry -- 19th century -- History and criticism; Religion in literature; Liturgy and poetry; Architecture and literature; Liturgy and architecture; Great Britain -- Church history -- 19th century